Prognostic impact of myosteatosis in patients with colorectal cancer: a systematic review and meta‐analysis. Issue 5 (1st June 2020) - Lee, Chan Mi; Kang, Jeonghyun
Abstract: Background: Myosteatosis has been reported to be a novel biomarker that could predict survival outcomes in patients with colorectal cancer. However, results have been conflicting. This systematic review and meta‐analysis aimed to evaluate the long‐term impact of myosteatosis on the survival of these patients. Methods: A systematic search of PubMed, Embase, and Cochrane up to 27 November 2019 generated 7022 records. Studies that reported hazard ratio (HR) for overall survival, cancer‐specific survival, or disease‐free survival based on myosteatosis or radiodensity were included. A total of 110 full‐text articles were considered for inclusion, and 14 were selected for qualitative analysis. Inverse variance method was used with random effects model for data analysis. Results: The total number of enrolled patients included in the meta‐analysis was 6518 for univariate and 8572 for multivariate HR analysis, from 12 and 10 studies, respectively. Patients with myosteatosis had a significant increase in overall mortality compared with non‐myosteatosis patients by both univariate analysis [HR 1.38, 95% confidence interval (CI) 1.21 to 1.58, P  < 0.00001] and multivariate analysis (HR 1.55, 95% CI 1.23 to 1.96, P  < 0.00001). In subgroup analysis based on studies that reported HRs of both sarcopenia and myosteatosis, the negative effect of myosteatosis on overall survival was independent of sarcopenia using univariate values (sarcopenia HR 1.48, 95% CI 1.14 to 1.91, P  = 0.003 vs. myosteatosis HR 1.51, 95% CI 1.17 to 1.96, P  = 0.002) and multivariate values (sarcopenia HR 1.28, 95% CI 1.09 to 1.49, P  = 0.002 vs. myosteatosis HR 1.38, 95% CI 1.07 to 1.80, P  = 0.001). Conclusions: This meta‐analysis demonstrates that myosteatosis is associated with worse overall survival in patients with colorectal cancer. More investigation is needed to standardize the measurement protocol for myosteatosis and to further optimize its prognostic power for colorectal cancer patients.